Effect of aging treatment on apparent hydrogen solubility and trapping in a new generation maraging steel. (1st July 2020) - Rousseau, Camille; Oudriss, Abdelali; Milet, Remy; Feaugas, Xavier; El May, Mohamed; Saintier, Nicolas; Tonizzo, Quentin; Msakni-Malouche, Mariem
Abstract: New generation maraging steel developed by the aeronautical industry meet the highest mechanical standards thanks to the controlled growth of M2 C carbides and B2-NiAl precipitates during aging treatment at around 500  °C. However, the literature has reported a low resistance of precipitation-hardened steel to hydrogen embrittlement that is associated with aging treatment and trapping at precipitates or reverted austenite. Thus, in relation to the complex microstructure of X23NiCoCr 13-6-3 maraging steel, hydrogen solubility and trapping was investigated using Thermodesorption Spectroscopy. A high apparent solubility of hydrogen was observed after aging that was attributed to reversible trapping at coherent B2-NiAl precipitates. Graphical abstract: Image, graphical abstract